Influência da laserterapia na proliferação de células-tronco do ligamento periodontal humano - Soares, Diego Moura (2013)
Low level laser irradiation (LLLI) has been used in Dentistry to promote wound healing and tissue regeneration. The literature shows a positive effect of LLLI on cell proliferation, but little is known about their effectiveness in promoting stem cells proliferation. The aim of this study was to evaluate the effect of LLLI on the proliferative rate of human periodontal ligament stem cells. Extracts of periodontal ligament were isolated from two third molars removed by surgical and/or orthodontic indication. After enzymatic digestion, the cells were grown in α-MEM culture medium supplemented with antibiotics and 15% fetal bovine serum. On the third subculture, the cells were irradiated with a InGaAlP-diode laser, using two different energy densities (0,5J/cm 2 - 16 seconds and 1,0J/cm² - 33 seconds), with wavelength of 660nm and output power of 30mW. A new irradiation, using the same parameters, was performed 48h after the first. A control group (non irradiated) was kept under the same experimental culture conditions. The Trypan blue exclusion test and the mitochondrial activity of the cells measured by MTT [3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide] essay were performed to assess the cell proliferation in the intervals of 0, 24, 48 e 72 h after irradiation. The data of cell counts were submitted to nonparametrical statistical tests (Kruskal-Wallis and Mann-Whitney), considering a confidence interval of 95%. DAPI (4 -6-Diamidino-2-phenylindole) staining of the cells was performed at 72h interval to evaluate possible nuclear morphological changes induced by LLLI. The results of this study show that the energy density of 1,0 J/cm² promoted greater cell proliferation compared to the other groups (control and 0,5 J/cm²) at intervals of 48 and 72h. The mitochondrial activity measured by MTT essay showed similar results to the Trypan blue cell counting test. The group irradiated with 1,0J/cm² exhibited a significantly higher MTT activity in the intervals of 48 and 72h, when compared to the group irradiated with 0,5J/cm². No nuclear morphological change was observed in the cells from the three groups studied. It is concluded that LLLI has stimulatory effects on the proliferation of human periodontal ligament stem cells. Therefore, the use of laser irradiation in this cell type may be important to promote future advances in periodontal regeneration